Fra normativ til historisk topos-forskning - Meiner, Carsten; Tygstrup, Frederik (K&K - Kultur og Klasse, 2017)
On the basis of Ernst Robert Curtius’ topology, Mikhail Bachtine’s theory of the chronotope, and Erich Auerbach’s analysis of “la cour et la ville”, this article envisions literary topology as the study of symbolic places in literary history.